Non-abelian brane worlds: the open string story - Blumenhagen, Ralph; Honecker, Gabriele; Weigand, Timo (Arxiv, 2005)
We extend the string model building rules for the construction of chiral supersymmetric Type I compactifications on smooth Calabi-Yau manifolds. These models contain stacks of D9-branes endowed with general stable U(n) bundles on their world-volume and D5-branes wrapping holomorphic curves on the Calabi-Yau.